Psychopharmacology of Williams syndrome: safety, tolerability, and effectiveness. Issue 3 (4th March 2021) - Thom, Robyn P.; Pober, Barbara R.; McDougle, Christopher J.
ABSTRACT: Introduction : Williams syndrome (WS) is a neurogenetic disorder characterized by a hyper-social personality, intellectual disability, and multiple medical co-morbidities. Psychiatric co-morbidities are also common. Since medical co-morbidities are common in this population, the risk-benefit of the use of psychiatric medications must be carefully considered and monitoring for safety and tolerability is needed. Areas covered : We review the cognitive profile and common medical co-morbidities in WS. We then discuss the common presentations of psychiatric disorders and review the available evidence on the use of psychiatric medications in WS. No prospective psychiatric medication trials have been conducted. We highlight the side effect profile of common psychiatric medications as they pertain to WS. Expert opinion : Psychiatric disorders can have a major effect on the quality of life of individuals with WS. The lack of long-term safety data and high likelihood of medical co-morbidities in WS make the judicious use of psychiatric medications more challenging; however, they can play an important role in decreasing distress and improving functioning. We provide recommendations for first– and second-line classes of medications based on our clinical experience and consideration of adverse effect profiles, as well as safety monitoring parameters at baseline and periodically.